PERANCANGAN MEDIA CETAK SEBAGAI MEDIA PROMOSI PADA KLINIK INSAN MEDIKA SEMARANG - Enggar Sulistiyono; Erlinda Sholihah (Lembaga Pengembangan Kinerja Dosen, 2021)
Clinic is a health service facility that provides individual health services that provide basic and/or specialist medical services, organized by more than one type of health worker (nurse and/or midwife) and led by a medical professional (doctor, specialist doctor, dentist or doctor). specialist dentist). One of them is the Insan Medika Clinic which serves health services including General Practitioners, Pediatricians and Gynecologists, so that they become a reference for treatment for the community. Over time, the Government held the National Health Insurance Program (JKN) – BPJS. The target market desired by the Insan Medika Clinic is not only from the lower classes but from all walks of life. With a very affordable price for a big city like Semarang, people flock to medical clinics for treatment. But in reality the Insan Medika Clinic is not well known. The lack of promotion is one of the reasons. The previous promotional media used only nameplates that were not able to reach the wider community. Moving on from the needs and objectives above, it is necessary to promote this Insan Medika Clinic. In this case the author uses print media which will make it easier for the public to find out about the Insan Medika Clinic. Print media used are leaflets and flyers. Keywords Business, Print Media, Promotional Media, Insan Medika Clinic Semarang